UHPLC-PDA Assay for Simultaneous Determination of Vitamin D3 and Menaquinone-7 in Pharmaceutical Solid Dosage Formulation - Muhammad Jehangir; Mahmood Ahmed; Muhammad Imtiaz Shafiq; Abdul Samad; Iftikhar-ul-Haq (Journal of Analytical Methods in Chemistry)
A newly developed method based on ultrahigh performance liquid chromatography (UHPLC) was optimized for the simultaneous determination of vitamin D3 and menaquinone-7 (MK-7) in tablet formulation in the present study. UHPLC separation of vitamin D3 and MK-7 was performed with ACE Excel 2 C18-PFP column (2 μm, 2.1 × 100 mm) at 0.6 mL min−1 flow rate, whereas the mobile phase consisted of methanol/water (19:1, v/v, phase A) and isopropyl alcohol (99.9%, phase B) containing 0.5% triethylamine. Isocratic separation of both the analytes was performed at 40°C by pumping the mobile phases A and B in the ratio of 50:50 (v/v, pH, 6.0). Both analytes were detected at a wavelength of 265 nm and the injection volume was 1.0 μL. The overall runtime per sample was 4.5 min with retention time of 1.26 and 3.64 min for vitamin D3 and MK-7, respectively. The calibration curve was linear from 5.0 to 100 μg mL−1 for vitamin D3 and MK-7 with a coefficient of determination (R2) ≥ 0.9981, while repeatability and reproducibility (expressed as relative standard deviation) were lower than 1.46 and 2.21%, respectively. The proposed HPLC method was demonstrated to be simple and rapid for the determination of vitamin D3 and MK-7 in tablets.